Modulation of lung inflammation and immune markers in asthmatic rats treated by Portulaca oleracea - Mahsa Kaveh; Akram Eidi; Ali Neamati; Mohammad Hossein Boskabady (Mashhad University of Medical Sciences, 2017)
Objective: Previous studies indicated anti-inflammatory effects for Portulaca oleracea in various inflammatory disorders. In this study, the effects of P. oleracea on bronchoalveolar lavage fluid (BALF) levels of total protein (TP), Phospholipase A2(PLA2) and IgE in sensitized rats were examined. Materials and Methods: Male rats were randomly divided into six groups namely, control (group C), sensitized rats (group S), sensitized animal treated with three concentrations of the extract of P. oleracea and dexamethasone (n = 8 for each group). The levels of TP, PLA2 and IgE in BALF were measured. Results:The levels of TP, PLA2and IgE were significantly increased in the BALF of group S compared to group C (pand IgE compared to group S (pand IgE (p Conclusion: The results indicated anti-inflammatory and immunomodulatory effects of P. oleracea in sensitized rats (as an animal model of asthma) which was equal or more marked than dexamethasone at studied concentrations.